High prevalence of enteroparasitosis in urban slums of Belo Horizonte-Brazil. Presence of enteroparasites as a risk factor in the family group. (1st September 2013) - Gil, Frederico F; Busatti, Haendel G N O; Cruz, Valeria L; Santos, Joseph F G; Gomes, Maria A
Abstract : The present study evaluates the prevalence of enteroparasitosis in the urban slums of Belo Horizonte, Brazil and the risk of transmitting enteroparasites to the family members of infected individuals. Stool samples were collected and examined at clinical laboratories near each slum. Individuals were identified and classified as positive for parasitosis (IP + ), and individuals with negative stool tests were classified as negative for parasitosis (IP − ) and enrolled as control patients. We collected samples from 594 patients, of which 20·2% and 79·8% were classified as IP + and IP −, respectively. In addition, 744 family members (FIPs) effectively participated in the study by providing fecal samples. In total, 1338 participants were evaluated. Of these, 34·6% were tested positive for parasitosis. Blastocystis was the most prevalent parasite, infecting 22·4% of individuals. Among FIPs, the overall prevalence was 46·1%. Of these, 50·6% and 44·7% were classified as FIPs + and FIPs −, respectively. These results showed that IP + did not impact the prevalence of infection within the studied communities, not constituting index cases of specific risk behaviors, suggesting that, in fact, these communities are exposed to similar oral-fecal routes of contamination.